The information science policy for the public open data of the national research institute - Donghun Yoon (Cogent Business & Management, 2017)
In modern society, the importance of information is constantly growing. Human life has been diversely changed due to the volume expansion of information handling and distribution. The rapid growth and informatization of information and communications technology (ICT) could be the driver of the production and distribution of information in the real world. Also, it has greatly influenced the economy, politics, society, culture, etc. As the value of information continues to increase, all governments around the world are becoming more and more interested in the reaction to the provision of information. The people need liberty and equality in the environment for the acquisition or utilization of necessary information. Especially due to the importance of the information sharing system, both the government and people are greatly interested in the information sharing policy of the government. Information sharing policies around the world greatly affect people. They disclose information (from government agencies, local government units, public institutions, etc.) to people. However, in the case of national research institutes, their information sharing policy has been ineffective due to the specialty of their work and data. Also, their data are not at the general information sharing level. In this paper, first, the information science policy for public open data of national research institutes is presented and discussed. First, we will look for an efficient method of information sharing policy-making for national research institutes. Then we will discuss and present research results data of national research institutes. These will comprise the most useful information from national research institutes. Also, the actual availability of the research results data will be discussed through their utilization trend analysis. In this paper, we propose the information science policy direction for public open data of national research institutes through a study of their information sharing system.
Keywords: 650